1997
DOI: 10.1002/(sici)1098-2337(1997)23:4<245::aid-ab3>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Cross-national comparison of children's attitudes towards bully/victim problems in school

Abstract: Using large‐scale survey data from Italy, and England, findings are reported for attitudes to school bullying; specifically the extent to which children expect their teachers, or other children, to intervene in bullying; and the extent to which children either empathise with victims of bullying, or state that they themselves would do something about it. Findings were broadly similar in most respects, in the two countries. Teachers were thought to intervene fairly often, other children more rarely. Most childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
104
0
17

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 17 publications
11
104
0
17
Order By: Relevance
“…In addition, implicit bullying attitudes interacted with explicit bullying attitudes in the prediction of additional variance in bullying behavior. The interaction indicated that implicit In line with previous research, we found that most children had relatively negative explicit bullying attitudes (Andreou et al 2005;Menesini et al 1997;Salmivalli and Voeten 2004) which corresponds to the anti-bullying policies of schools and bullying programs. In accordance with our expectations, children's explicit bullying attitudes were also related to their bullying behavior.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, implicit bullying attitudes interacted with explicit bullying attitudes in the prediction of additional variance in bullying behavior. The interaction indicated that implicit In line with previous research, we found that most children had relatively negative explicit bullying attitudes (Andreou et al 2005;Menesini et al 1997;Salmivalli and Voeten 2004) which corresponds to the anti-bullying policies of schools and bullying programs. In accordance with our expectations, children's explicit bullying attitudes were also related to their bullying behavior.…”
Section: Discussionsupporting
confidence: 88%
“…Strikingly, until now bullying research and programs have only focussed on explicit bullying attitudes (these attitudes are most often assessed on likert-scales, asking children to what extent they agree with various statements on bullying; Boulton et al 2002;Menesini et al 1997;Salmivalli and Voeten 2004) and their relation to bullying behavior (see for a review Stevens et al 2000). These studies show that the majority of school-aged children have a negative explicit bullying attitude whereas only a minority have a positive explicit bullying attitude (e.g.…”
mentioning
confidence: 99%
“…We expect girls to be more assertive than boys, who will more often choose retaliation as an effective means. We based our hypotheses on the fact that girls condemn bullying and feel upset by it more often than boys (Menesini et al, 1997). It is therefore possible that their solutions are stricter vis-à-vis the bully.…”
Section: Hypothesesmentioning
confidence: 99%
“…Participants included 1,398 students in fifth-grade classrooms in Australia (n = 130), Canada (n = 412), Japan (n = 302), Korea (n = 436), and United States (n = 118). Previous research indicates that bullying behavior is particularly evident within this age group, grade 5 to 7 age range, (Menesini et al, 1997;Morita et al, 1999;Nansel et al, 2001). Other research indicates that bullying decreases somewhat at later ages (Whitney & Smith, 1993).…”
Section: Methods Participantsmentioning
confidence: 84%